Pengembangan Keterampilan Siswa Melalui Pelatihan Robotik Untuk Mendukung Agenda Sustainable Development Goals (SDGs) - Soni Prayogi; Teguh Aryo Nugroho; Nita Indriani Pertiwi; Wahyu Agung Pramudito; Marza Ikhsan Marzuki; Muhammad Abdillah; Wahyu Kunto Wibowo; Herminarto Nugroho; Teuku Muhammad Roffi; Muhammad Muhammad (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
ABSTRACT This Community Service Activity aims to improve students' technical skills in robotics while supporting SDGs, especially quality education and technological innovation. Training includes robotics assembly, programming, and applications, with an interactive approach tailored to the curriculum. The program begins with the identification of partner schools with limited resources, followed by coordination and preparation of training modules. Students learn basic robotics theory including the principles of electronics, mechanics, and programming, as well as the practice of assembling and programming robots in small groups. Internal competitions are held to test students' abilities and motivate them to solve problems creatively. The main challenges include limited facilities and time, overcome by adjusting materials and schedules. Evaluations show significant improvements in student skills, with creative innovations in technology-based solutions to support SDGs. The program has succeeded in generating students' interest in technology, providing a strong foundation for similar programs in the future, and encouraging collaboration between education and industry.